Cluster-randomised trial of community-based screening for eye disease in adults in Nepal: the Village-Integrated Eye Worker Trial II (VIEW II) trial protocol. Issue 10 (15th October 2020) - O'Brien, Kieran S; Stevens, Valerie M; Byanju, Raghunandan; Kandel, Ram Prasad; Bhandari, Gopal; Bhandari, Sadhan; Melo, Jason S; Porco, Travis C; Lietman, Thomas M; Keenan, Jeremy D
Abstract : Introduction: The majority of blindness worldwide could be prevented or reversed with early diagnosis and treatment, yet identifying at-risk and prevalent cases of eye disease and linking them with care remain important obstacles to addressing this burden. Leading causes of blindness like glaucoma, diabetic retinopathy and age-related macular degeneration have detectable early asymptomatic phases and can cause irreversible vision loss. Mass screening for such diseases could reduce visual impairment at the population level. Methods and analysis: This protocol describes a parallel-group cluster-randomised trial designed to determine whether community-based screening for glaucoma, diabetic retinopathy and age-related macular degeneration reduces population-level visual impairment in Nepal. A door-to-door population census is conducted in all study communities. All adults aged ≥60 years have visual acuity tested at the census visit, and those meeting referral criteria are referred to a local eye care facility for further diagnosis and management. Communities are subsequently randomised to a community-based screening programme or to no additional intervention. The intervention consists of a single round of screening including intraocular pressure and optical coherence tomography assessment of all adults ≥60 years old with enhanced linkage to care for participants meeting referral criteria. Four years after implementation of the intervention, masked outcome assessors conduct a repeat census to collect data on the primary outcome, visual acuity. Individuals with incident visual impairment receive a comprehensive ophthalmological examination to determine the cause of visual impairment. Outcomes are compared by treatment arm according to the originally assigned intervention. Ethics and dissemination: The trial has received ethical approval from the University of California San Francisco Institutional Review Board, Nepal Netra Jyoti Sangh and the Nepal Health Research Council. Results of this trial will be disseminated through publication in peer-reviewed journals and presentation at local and international meetings. Trial registration number: NCT03752840